2014
DOI: 10.17221/574/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of site-specific weed management in winter crops on yield and weed populations

Abstract: Site-specific weed management (SSWM) methods allow spatially variable treatment of weed populations according to actual weed abundance, thus offering the opportunity for herbicide savings. However, SSWM's effect on weed population dynamics is not sufficiently understood. In this study, SSWM was conducted based on various application thresholds to analyse the effects on crop yield and weed infestation in the succeeding crop. SSWM was used on a 3.07 ha experimental field in winter wheat (2011) and winter oilseed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Potato is propagated vegetatively, which exposes the crop plant to numerous harmful factors (weeds, pests, viral, fungal and bacterial diseases). As a result of reduced soil tillage and simplified harvest, delayed planting dates, natural manuring and continuous cropping, an increase in weed infestation of fields planted to potato has been observed [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Potato is propagated vegetatively, which exposes the crop plant to numerous harmful factors (weeds, pests, viral, fungal and bacterial diseases). As a result of reduced soil tillage and simplified harvest, delayed planting dates, natural manuring and continuous cropping, an increase in weed infestation of fields planted to potato has been observed [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the spatial stability of weed populations, Pearson's correlation coefficient was calculated for densities of weed groups between 2011 and 2014. Other details on methods can be found in Hamouz et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…In previous work (Hamouz et al 2013(Hamouz et al , 2014, it was shown that SSWM applied to winter cereals and winter oilseed rape had no significant effect on crop yields. The present work evaluates the effect of SSWM on weed populations over a 4-year period based on various threshold values.…”
mentioning
confidence: 93%
“…Since it is only when infestation surpasses 7.4% that immediate intervention is necessary, this breakdown of a field into areas of low, intermediate and high levels of infestation makes it possible to construct herbicide treatment maps identifying where intervention is needed (Gerhards et al, 2002;Longchamps et al, 2012), with the insertion of such maps in equipment performing localized applications promoting economy in herbicide use (Shiratsuchi et al, 2003). Evaluating a system of images to help in making decisions about intervention in the control of weeds, Hamouz et al (2014) identified a potential reduction of up to 90% in the volume of herbicides needed in comparison with what was recommended by a more conventional method. For Rizzardi and Fleck (2004), densities of 4 or more plants per m -2 of the common weed Bidens pilosa L. can limit the development of soybeans.…”
Section: Weed Infestation Level Based On Expert Evaluationmentioning
confidence: 99%